Leptophlebiidae (Ephemeroptera) of the Serra do Tepequém, Roraima State, Brazil: new records and description of two new species - Neto, Jaime De Liege Gama; Hamada, Neusa (Zootaxa, 2014)
Miroculis (Miroculis) eldorado sp. nov. and Ulmeritoides passorum sp. nov. are described based on material from Serra do Tepequém, Roraima State, Brazil. Additional records of Leptophlebiidae genera and species are made. Askola Peters, 1969, Farrodes Peters, 1971, Microphlebia Savage & Peters, 1983, Hydrosmilodon Flowers & Dominguez, 1992, Hagenulopsis minuta Spieth, 1943 and Simothraulopsis demerara (Traver, 1947) are recorded for the first time in Roraima State. Simothraulopsis janae Mariano, 2010 is recorded for the first time in the Northern Brazil.